FRAMEWORK LEARNING MANAGEMENT SYSTEM BERBASIS MICROLEARNING UNTUK MENINGKATKAN EFEKTIVITAS PEMBELAJARAN PADA PENDIDIKAN NON-FORMAL (STUDI KASUS PADA LKP) - Saputro, Indrawan Ady; Aziz, Riyan Abdul; Widiyanti, Sri; Purwidiantoro, Moch Hari (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2026)
The rapid development of digital learning technologies requires innovative systems that can improve learning effectiveness, particularly in non-formal education institutions such as Training and Course Centers (LKP). However, existing learning systems often lack structured mechanisms to ensure gradual, measurable mastery of competencies. Therefore, a microlearning-based Learning Management System (LMS) integrated with a sequential mastery approach is proposed. This study aims to design and implement a microlearning-based LMS to enhance learning effectiveness in non-formal education settings. The system supports step-by-step delivery of learning to ensure progressive achievement of competency. The research methodology includes requirements analysis, system design using the Unified Modeling Language (UML), web-based implementation, and system evaluation using Black-Box Testing, the System Usability Scale (SUS), and pre- and post-test assessments. The results show that all system functions operate as intended. The usability evaluation obtained a SUS score of 78.33, categorized as Good and Acceptable. Learning effectiveness increased significantly, with an average score improvement of 25.67 points (45.03%) and an N-Gain value of 0.60 (moderate category), while achieving a 100% completion rate. In conclusion, the developed LMS is feasible and effective in improving learners’ competencies in non-formal education environments and offers a practical solution for digital learning transformation in LKP.